Algunos hongos interesantes encontrados en Catalunya - Tabarés Carriedo, Manuel; Santamaria i del Campo, Sergi (Revista Catalana de Micologia, 2016)
SOME INTERESTING FUNGI COLLECTED IN CATALONIA. Seven rarely collected species from Catalonia are here reported. Descriptions, iconography and comments are included for each taxon. Micrographs are also added when considered necessary. There are four Basidiomycota: Bovista ochrotricha, Crepidotus malachius var. trichifer, Gastropila fragilis, and Rectipilus fasciculatus; and three Ascomycota: Hymenoscyphus repandus, Hymenoscyphus scutula, and Ramsbottomia asperior.